Uterine Natural Killer Cells in the Context of Implantation: Immunohistochemical Analysis of Endometrial Samples from Women with Habitual Abortion and Recurrent Implantation Failure - Lapides, L; Klein, M; Belušáková, V; Csöbönyeiová, M; Varga, I; Babál, P (Physiological research, 2022)
Infertility affects approximately 48 million couples globally. Despite the enormous progress of the methods of reproductive medicine that has been made since the first test-tube baby was born in 1978, the implantation rate of day-3 embryos is only around 15-20 % and 30 % of day-5 embryos. Numerous strategies aim to improve implantation rates and prevent repeated implantation failure, however there is no specific general recommendation leading to satisfying results. One of the many risk factors relevant in this regard is the uterine immunological make-up, mainly the uterine Natural Killer (uNK) cells. They orchestrate the overall immune response during implantation by influencing trophoblast invasion and vascular remodeling and throughout pregnancy, uNK cells are also the main immune cells at the maternal-foetal interface. Previously, uNK count has been correlated with various fertility issues including idiopathic reccurent miscarriage. The present study used endometrial samples collected from 256 patients with recurrent implantation failure (RIF), habitual abortion (HA) and idiopathic sterility. Samples were collected between day 19 and 21 of the menstrual cycle mainly by Pipelle endometrial sampling. The samples were fixed in formalin for 24 hours and further processed for immunohistochemistry using anti-CD56 to visualize this antigen marker of uNK cells. Immunohistochemical counting was performed to assess the low, normal, or elevated count of uNK cells. According to the one-way ANOVA test, the age of our patients did not have any influence on the count of uNK cells. With Spearman correlation analysis, we found statistically significant correlation (p-value 0.05) of -0.133 between prior miscarriage and lower uNK cell count. Using the same analysis we found statistically significant correlation (correlation 0.233 with p-value 0.01) between number of uNK cells and activation status. Patients with higher uNK cells were more frequenty diagnosed with endometriosis (p-value 0.05, correlation 0.130). Patients with an immunological factor of sterility (defined by a clinical immunologist) had a lower chance of gravidity (-0.203 with p-value 0.01). Based on our results, we can confirm that there is a correlation between RIF, HA, idiopathic sterility, endometriosis, and immunological factor of sterility (uNK cell count). The true predictive value with regard to fertility outcomes needs to be addressed in future research.
Keywords: uterus; Pregnancy; Humans; lidé středního věku; Female; lidé; buňky NK; Uterus; Killer Cells, Natural; infertilita; Embryo Implantation; ženské pohlaví; endometrióza; habituální potrat; Middle Aged; Abortion, Habitual; těhotenství; implantace embrya; Endometriosis; Infertility